Association between insulin resistance and acanthosis nigricans in obese children in a tertiary care hospital in Lima, 2018 - 2019 - Bardellini Ortiz, Miguel (2020)
Objective: to explore whether there is an association between the frequency of insulin resistance and the presence and distribution of acanthosis nigricans in obese children. Materials and methods: this is a cross-sectional study in which 42 obese children between 5 and 10 years of age participated. The presence of acanthosis nigricans was characterized (number and distribution of affected areas) as well as other variables, such as age, sex, and Body Mass Index. Four groups were formed, and the frequency of insulin resistance was determined, aiming to explore its association with the other variables. Results: mean participants’ age was 8.6 years, and male subjects accounted for 54.8%. Nearly two-thirds of participants (64.3%) had acanthosis nigricans, and 78% of them had insulin resistance. Associated variables with statistical significance were age (p= 0.009), BMI (p= 0.025), and the presence of acanthosis nigricans affecting the neck region. Conclusions: there is an association between insulin resistance and the presence of acanthosis nigricans affecting the neck of obese children.